Evaluation of the influence of mechanical pruning in the performance of the row-side continuous canopy shaking harvester prototype - Dias, A.B.; Falcão, J.; Pinheiro, A.; Peça, J. (Acta Hortic., 2023)
In high density olive orchards, mechanical harvesting is made by trunk shaking requiring a high demand of manual labour. The use of adapted over-the-row grape harvesters is not available in these groves due to large canopies dimension. A prototype based on the side row concept was developed. The prototype comprises two symmetrical harvesters trailed by a farm tractor. Each harvester has a vibratory rotor with flexible rods, a catching platform with conveyor belts delivering fruits to a temporary storage bag. From 2015 to 2018, authors carried out a trial to evaluate the adequacy of olive canopy based on mechanical pruning in the performance of the prototype. The trial was established in an irrigated olive orchard of the ‘Picual’ cultivar planted with the array 7×3.5 m. In a randomized complete block design with three replications, three treatments are being compared leading to 9 plots with 30 trees plot-1. The treatments under study are: T1 – mechanical pruning: topping the canopy parallel to the ground at 3.5 m high in 2015 and 3.3 m in 2017; hedging the two sides of the canopy in 2015 at 1.4 m from the tree trunk; T2 – mechanical pruning: topping the canopy parallel to the ground at 3.5 m high in 2015 and 3.3 m in 2017; hedging the two sides of the canopy in 2015 at 1.0 m from the tree trunk; T3 – mechanical pruning + manual pruning complement: topping the canopy parallel to the ground at 3.5 m high in 2015 and 3.3 m in 2017; hedging the two sides of the canopy in 2015 at 1.0 m from the tree trunk; manual pruning complement in 2015 to remove wood in the external faces of the canopy and in 2017 to remove wood suckers inside the canopy. Regarding the olive removal efficiency, significant differences were registered between years, but no significant differences were found among treatments in each year.
Keywords: mechanical harvesting; high density olive groves; pruning